The Effect of the Government Internal Control System on the Performance of Government Agencies - Saputra, Ade; Setiawan, Ade Budi; Jamaludin, Ayi (Institut Bisnis dan Informatika Kesatuan, 2024)
This study aims to analyze the impact of the Government Internal Control System, budget, and organizational commitment on the performance of government agencies in Bogor City. Using a descriptive survey method, this study involves 36 Regional Government Organizations, with 10 Regional Government Organizations purposively selected as the sample. Data were collected through questionnaires, and results were analyzed using multiple linear regression to test the hypotheses. The findings indicate that Internal Control System, budget, and organizational commitment significantly influence government agency performance, both overall and partially. The combined influence of these three variables on the performance of government agencies in Bogor City reaches 44.5%. These findings highlight the importance of effective Internal Control System implementation, adequate budget allocation, and strong organizational commitment in improving government performance. This study contributes by providing insights for policymakers in Bogor City to strengthen these aspects to achieve more optimal governmental performance.